2010
DOI: 10.1021/ja108586d
|View full text |Cite
|
Sign up to set email alerts
|

Platinum(II)-Catalyzed Generation and [3+2] Cycloaddition Reaction of α,β-Unsaturated Carbene Complex Intermediates for the Preparation of Polycyclic Compounds

Abstract: Pt(II)-catalyzed generation of unsaturated carbene complex intermediates from various propargyl ether derivatives based on electrophilic activation of alkynes was realized. These in situ generated unsaturated carbene complexes undergo [3+2] cycloaddition reaction with various vinyl ethers, leading to efficient formation of indoles, naphthols, and benzofuran fused with a five-membered ring in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(42 citation statements)
references
References 28 publications
1
41
0
Order By: Relevance
“…Then, using methanol and/or water as nucleophile a variety of functionalized indenes 10 with selected substitution at R 1 , R 2 and R 3 were synthesized (entries 7-19). As expected by the results obtained in the cycloisomerization in the absence of nucleophile the reaction tolerates both electron-withdrawing (entries 7-10) and electron-donating (entries [11][12] groups at the internal phenyl ring as well as a broad range of substituents at the triple bond including (hetero)aromatic (entries 7-14), (cyclo)alkyl (entries 15-18), and heteroatomic moieties (entry 19). All these reactions were completely selective and we did not observe the formation of additional products derived from other possible reaction pathways.…”
Section: Synthesis Of Oxygen-functionalized 1h-indenessupporting
confidence: 57%
See 2 more Smart Citations
“…Then, using methanol and/or water as nucleophile a variety of functionalized indenes 10 with selected substitution at R 1 , R 2 and R 3 were synthesized (entries 7-19). As expected by the results obtained in the cycloisomerization in the absence of nucleophile the reaction tolerates both electron-withdrawing (entries 7-10) and electron-donating (entries [11][12] groups at the internal phenyl ring as well as a broad range of substituents at the triple bond including (hetero)aromatic (entries 7-14), (cyclo)alkyl (entries 15-18), and heteroatomic moieties (entry 19). All these reactions were completely selective and we did not observe the formation of additional products derived from other possible reaction pathways.…”
Section: Synthesis Of Oxygen-functionalized 1h-indenessupporting
confidence: 57%
“…Therefore, we were pleased to find that, after some optimization, [42] we were able to obtain indene derivatives with good enantiomeric excess using the combination (S)-3,5-xylyl-MeOBIPHEP-(AuCl) 2 / AgOTs as catalyst in dichloromethane at -30 ºC (Table 6). Under these optimized catalytic conditions we found high yields and enantioselectivities for o-(alkynyl)styrenes 3a-e,6a-b where R 5 is an aromatic or heteroaromatic group (entries [1][2][3][4][10][11]. Interestingly, the possibility of increasing the enantiomeric excess of the final 8 products by a simple recrystallization has been demonstrated for indene 7b that we were able to isolate with 92% ee (entry 11).…”
Section: Enantioselective Synthesis Of 1h-indenesmentioning
confidence: 79%
See 1 more Smart Citation
“…[10,11] Similarly, vinyl Fisher carbenes [12] or vinyl gold carbenes derived from propargylic esters [13] can also react with dienes to form various seven-membered rings. It was recently reported that vinyl metal carbenes could be conveniently generated from propargylic ethers tethered with a nucleophile for a [3+2] cycloaddition [14] and a synthesis of furans. [15] We envisioned that the vinyl metal carbene 2 , derived from 1 , would undergo a formal [4+3] cycloaddition [16] with diene 3 to afford the cyclohepta[ b ]indole 4 by either a cyclopropanation/Cope rearrangement sequence involving the divinyl-cyclopropane 5 , or an unusual [4+4] cycloaddition to form the eight-membered metallacycle 6 with subsequent reductive elimination.…”
mentioning
confidence: 99%
“…[14,15] A low yield of 4a or no product, however, was observed using these catalysts (Table 1, entries 5–8). We suspect that the coordination of the bidentate diene 3a to PtCl 2 may reduce the acidity of the metal.…”
mentioning
confidence: 99%